Pola Konsumsi, Paritas, dan Aktivitas Fisik dengan Kejadian Anemia Wanita Usia Subur di Komunitas Adat Terpencil Suku Anak Dalam - Asparian Asparian; Silvia Mawarti Perdana; Lia Nurdini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between consumption patterns, parity, and physical activity with the incidence of anemia in women of childbearing age in the Remote Indigenous Community of Tribe Children in the Terap River Basin, Batanghari Regency, Jambi Province. This research method is quantitative research with a cross-sectional study design. The results showed that the prevalence of anemia in the respondents amounted to 64.7 percent. As many as 61.8 percent and 88.2 percent of respondents rarely consume animal and vegetable protein foods. Meanwhile, 73.5 percent of respondents often consume vegetables and fruit. More than half of the respondents (64.7%) have parity data of 3 people. A total of three-quarters of respondents (76.5%) have physical activity in the heavy category. In conclusion, there is a relationship between the consumption of fruit and vegetables and physical activity with the incidence of anemia in women of childbearing age. Keywords: Physical Activity, Anemia, Remote Indigenous Communities, Consumption, Parity